Situating science in Africa: The dynamics of computing research in Nairobi and Kampala. (February 2019) - Harsh, Matthew; Holden, Kerry; Wetmore, Jameson; Zachary, G Pascal; Bal, Ravtosh
Since the turn of the century, both Kampala and Nairobi have experienced a dramatic growth of computer science research, challenging accepted views of science in Africa. We deploy qualitative methods to follow active computer science researchers, graduate students, policy makers, administrators and entrepreneurs, in order to understand how computer science is enacted in these two cities. Our analysis focuses on four interrelated areas of labor, institutions, identities and scale. We illustrate the dynamics and frictions of computer science research across these areas, revealing the interlacing of moral economies of science and the political economy of higher education, the management of precarious professional lives and desire to get research done, and the pluralistic imaginations and multiple scales of computer science. Urban centers in East Africa are increasingly active in supporting granular and connective research communities that are socially transformative in ways that challenge conventional views of Africa as technologically dry. In this way, the computer science communities of Nairobi and Kampala are instructive for thinking about new geographies of science and technology studies.